Ecological features of mangroves as indicators of seawater intrusion - Suyadi ,; M. Basyuni; R. Amukti; C. Damayanti; D. Stokes; A. Mubaraq; Y.I. Rahmila (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Water filters are important ecosystem services in mangroves, playing an essential role in mitigating seawater intrusion and groundwater water management. However, ecological features that can be used as indicators of seawater intrusion in mangroves and the extent of mangroves’ role in groundwater quality management in coastal areas are not well identified. This study aimed to determine mangroves ecological features that can serve as indicators of seawater intrusion.METHODS: A geographic information system and geo-electric method were used, and remote sensing, vegetation survey, sample collection, and interview survey were performed.FINDINGS: Seawater intrusion is the major problem affecting groundwater quality in coastal areas, especially mall islands. A structural equation model revealed that mean mangrove patch thickness, mean mangrove patch density, soil resistivity, soil porosity, and tree density explained 80–95 percent of the variation in seawater intrusion during wet and dry seasons in the entire study area. Seawater intrusion decreased with increasing mean patch thickness of the mangrove but increased with increasing mangrove patch density. That is, the landscape metrics of mangroves, such as mangrove patch thickness and density, were associated with type when substrate or soil and tree density were good ecological indicators of seawater intrusion. Using landscape metrics as ecological indicators is a relatively quick, cheap, and easy-to-apply method.CONCLUSION: This study pioneers the use of novel landscape metrics—mean patch thickness and patch density—as ecological indicators of seawater intrusion, providing a quantitative framework that bridges mangrove structural attributes, soil characteristics, and collective influence on groundwater salinity regulation.